Editing and Noting: Vision and Revisions of Leigh Hunt's Literary Lives - Bugajski, Ken (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis essay examines Leigh Hunt’s three major autobiographical texts: Lord Byron and Some of His Contemporaries (1828), The Autobiography of Leigh Hunt (1850), and the second edition of the Autobiography (1860). From the earliest to the latest of these texts, Hunt transforms himself from the controversial author of The Story of Rimini and famous theatre critic to an editor of essay collections with a fading literary reputation. In both versions of the Autobiography, Hunt reuses and revises previously published passages, and these alterations highlight his changing self-image, especially his movement away from the literary spotlight.